Educating the whole child : cross-curricular skills, themes, and dimensions (Buckingham : Open University Press, 1995)
Cross-curricular skills, themes and dimensions: an introduction. Little citizens: helping children to help each other. Effective schooling for all: the 'special educational needs' dimension. Racial equality education: identity, curriculum and pedagogy...
Keywords: Education; Primary Education; Curriculum planning; Education, Primary -- Great Britain -- Curricula; Curriculum planning -- Great Britain; Education, Primary -- Great Britain -- Aims and objectives; Education, Primary -- Aims and objectives; Education, Primary -- Social aspects -- Great Britain; Education, Primary